Intra-Dialysis Hypotension in Patients Undergoing Hemodialysis - Naseri, Mitra; Azarfar, Anoush; Rasuli, Zahra (Journal of Pediatric Nephrology, 2019)
Introduction: Intra-dialysis hypotension occurs in 20- 55% of hemodialysis sessions. We aimed to define the prevalence and impact of pre-dialysis blood pressure, inter-dialysis weight gain, vasodilator agents, and characteristics of dialysis, serum calcium, and adjusted calcium, sodium, and albumin levels on intra-dialysis hypotension. Materials and Methods: In an observational prospective study, 44 hemodialysis cases aged 4.8-25 years were evaluated in 552 dialysis sessions. A decrease in the mean arterial blood pressure ≥ 10 mm Hg was defined as intra-dialysis hypotension. The characteristics of the patients were compared between cases and those without intra-dialysis hypotension. Results: Intra-dialysis hypotension was noted in 61.4% of the cases and 24.6% of the dialysis sessions. The duration of hemodialysis, weight gain between dialysis sessions, using vasodilator medications, serum sodium and adjusted calcium levels were compared between IDH + and IDH – cases. No significant differences were found in these variables between the 2 groups (P> 0.05 for all). Intra-dialysis hypotension was significantly more prevalent in cases with normal versus high systolic and diastolic blood pressure (P=0.014 and P=0.005 respectively). Intra-dialysis hypotension was significantly more frequent in girls, anuric patients, and patients with a history of transplantation (p=0.022, 0.011 and 0.008 respectively). A Significantly lower serum albumin concentration was found in cases with intra –dialysis hypotension (P=0.021). Conclusions: Intra-dialysis hypotension is a common complication of hemodialysis and is more prevalent in girls, normotensive patients, subjects with lower serum albumin concentrations, cases with a history of transplantation, and anuric patients. Keywords: Hemodialysis; Blood Pressure; Hypotension; Serum Albumin; Serum Calcium.